Aplikasi Pemesanan Papan Bunga Dan Spanduk Di Kabupaten Pidie Berbasis Android - Arif Gunawan; Yuswardi (Yayasan Sagita Akademia Maju, 2024)
The Application for Ordering Flower Boards and Banners is a tool to make it easier for sellers to market in the process of ordering and selling this product, the large number of residents in the Pidie Regency triggers requests to order quite a lot of flower boards and banners when there are daily events in Pidie district, so that making this Android-based application will help sellers and buyers because there is a system engaged in selling flower boards and banners. This system is an operating system designed for touchscreen mobile devices, such as smartphones and tablets. So there are lots of programmers who flock to make applications or modify this operating system in the community.